The role of the hippocampus in prediction and imagination.[article]. - Buckner, Randy L.
Traditionally,the hippocampal system has been studied in relation to the goal of retrieving memories about the past. Recent work in human and rodents suggests that the hippocampal system maybe better understood as a sytem that facilitates prediction about upcoming events. The hippocampus and associated cortical structures are active when people envision future events, and damage that includes the hippocampal region impairs this ability. In rats, hippocampal ensembles preplay and replay event sequences in the absence of overt behavior. If strung together in novel combinations, these sequences provide the neural building blocks for simulating upcoming events during decision-making, planning, and in imagining novel scenarios, Moreover, in both humans and rodents, the hippocampal system is spontaneously active during task-free epochs and sleep, further that suggesting that the system maynuse idol moments to derive new representations that set the context for future behaviors.